Strategi Pembinaan untuk Meningkatkan Profesionalisme Guru di Sekolah - Qusairi, Ahmad (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This research aims to identify and analyze the principal's strategy for fostering teacher professionalism at Zainul Jadid Middle School, Masalembu District, Sumenep Regency, Madura. Education is considered an important foundation for a country's development, with the main aim of educating and empowering individuals to contribute positively to society. The principal plays a key role in improving teacher professionalism through various strategies such as giving direction, correcting behavior, praising, accepting recommendations, maintaining identity, welcoming new members, and building group discipline. This study employs a qualitative descriptive method, with data collection techniques involving interviews and direct observation in the field. The research results show that school principals are active in involving teachers in training, workshops, and regular meetings to improve their competence and professionalism. The principal also emphasized the importance of structured supervision and guidance to ensure the effectiveness of the learning process. These findings highlight the important role of principals in creating a positive educational environment and supporting teacher professional development.